2020
DOI: 10.24002/kinerja.v24i2.2419
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Turnover Intention: Moderation of Organizational Trust and Organizational Justice

Abstract: This study aims to analyze the role of organizational trust and organizational justice in moderating the effect of job satisfaction on turnover intention. The population in this study are employees in several information technology companies in Jakarta. The research sample amounts to 195 respondents. Data collection method is done through a questionnaire. Data analysis method uses structural equation modeling-partial least square (SEM-PLS). The results of this study prove that job satisfaction a negative affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…It was shown that TI was inversely related to JS, indicating that JS of counselors significantly influences their career retention and the decision to stay within the profession This result agrees with those of previous studies (Chiedu et al, 2022; Nurhayati et al, 2020; Olsen & Huang, 2019). Specifically, JS is not merely an emotional experience but also reflects counselors’ perceptions of their work environment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was shown that TI was inversely related to JS, indicating that JS of counselors significantly influences their career retention and the decision to stay within the profession This result agrees with those of previous studies (Chiedu et al, 2022; Nurhayati et al, 2020; Olsen & Huang, 2019). Specifically, JS is not merely an emotional experience but also reflects counselors’ perceptions of their work environment.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in one study, Arif (2018) found that employees who are deeply embedded in the organization and believe that they are treated fairly by management are less likely to consider leaving. Nurhayati et al (2020) analyzed that the impact of distributive justice on TI is stronger among employees with high levels of JE. Furthermore, Karatepe and Shahriari (2014) also point out that, when combined with job embedding, OJ could also lessen TI.…”
Section: Jsmentioning
confidence: 99%
See 1 more Smart Citation
“…This comprehensive approach can help researchers better understand how CSR influences employees (Jones, 2010;Kroh, 2014), and how it links to the organization's goals (De Roeck and Maon, 2018;El Akremi et al, 2018). Many studies have explored the connection between how CSR is perceived and different employee outcomes, like job satisfaction (De Roeck et al, 2014;Valentine and Fleischman, 2008), employee loyalty (Lee and Kim, 2015;Rupp et al, 2013), and the intention to leave the job (Nurhayati et al, 2020).The study by Hashem, Fakhari, and Naftchli (2023) found that banks that are more socially responsible tend to perform better financially.…”
Section: Introductionmentioning
confidence: 99%